Peran Syekh Abdul Halim Khatib dalam Penyebaran Islam di Mandailing Natal, 1906-1991 - Muhammad Ridwan Nasution; Solihah Titin Sumanti; Kasron Muchsin (Medan Resource Center, 2022)
This article aims to see how the role of Sheikh Abdul Halim Khatib in the spread of Islam in Mandailing Natal. Sheikh Abdul Halim Khatib is a major scholar figure who is quite well known in Mandailing Natal and its surroundings. However, the role of Sheikh Abdul Halim Khatib in developing the religion of Islam, especially in Purbabaru, the people there participated in many recitations, and the people there were more active in religion. The researcher aims to find out the historical process of the entry and development of Islam in Mandailing Natal, the life of Sheikh Abdul Halim Khatib and his role in the development of Islam in Mandailing Natal and the writings of Sheikh Abdul Halim Khatib in spreading Islam in Mandailing. The research that the author is doing is field research using historical research methods, and this research was conducted in Purbabaru Village, Lembah Sorik Marapi District, Mandailing Natal Regency, and the informants in this study were Musthafawiyah alums who were considered more knowledgeable about the role of Sheikh Abdul Halim Preacher. Sheikh Abdul Halim Khatib's relationship with the community is different from that of his teacher, Sheikh Musthafa Husein because he teaches more in the classroom, such as giving recitations at home to the community and his students on a scheduled basis, and Sheikh Abdul Halim Khatib has knowledge in the field of Sufism.